2016
DOI: 10.1007/s10549-016-3860-6
|View full text |Cite
|
Sign up to set email alerts
|

Measured adolescent body mass index and adult breast cancer in a cohort of 951,480 women

Abstract: Body mass index (BMI) in adolescence, studied predominantly as a self-reported risk factor for breast cancer (BC), may have been subjected to recall bias. We examined the association between measured BMI in adolescence and the incidence of BC by menopausal status. 951,480 Jewish Israeli females aged 16-19 who underwent anthropometric measurements in 1967-2011 were followed up to 31.12.2012 for BC incidence. Cox proportional hazards models assessed the association between adolescent BMI (as age-specific CDC per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…A nested case–control study that used the data from the Nurses' Health Study and the Nurses' Health Study II was further excluded; instead, we included two studies from the same populations that further reported risk estimates by menopausal status. Finally, 24 publications were eligible for inclusion in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A nested case–control study that used the data from the Nurses' Health Study and the Nurses' Health Study II was further excluded; instead, we included two studies from the same populations that further reported risk estimates by menopausal status. Finally, 24 publications were eligible for inclusion in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four studies were included in this meta‐analysis, which assessed body fatness at a young age and the risk of breast cancer. In the meta‐analysis of combined premenopausal and postmenopausal women, the summary RR for each 5 kg m −2 increase in BMI was 0.86 (95% CI 0.82, 0.90) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In FBC, however, the relationship with adolescent BMI is inverse for premenopausal events . The reason may be the negative feedback on the hypothalamic‐pituitary axis caused by the high basal levels of circulating ovary‐produced estradiol in addition to the peripheral fat tissue synthesized hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we had no data to test this hypothesis. In women, SES and education were positively associated with FBC . A 1997 IARC publication focusing on social inequalities and cancer stated that while differences in cancer incidence are seen within industrialized countries by SES, the evidence is very limited as to which socioeconomic factors are of most importance, or whether it is the overall “package” of social inequality that mostly matters…”
Section: Discussionmentioning
confidence: 99%